The Strategy of Bank Sumut Sharia Sub-Branch Office HM Yamin Medan in Maintaining Customer Loyalty Amid the Decline in Funding Product Returns - Endang Suriyani Munthe; Wahyu Syarvina; Muhammad Arif (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to analyze the strategy of Bank Sumut KCP Syariah HM Yamin Medan in maintaining customer loyalty amid the decline in returns on funding products. This research employs a qualitative approach using a case study method. Data collection was conducted through in-depth interviews, observations, and documentation involving informants consisting of account officers, customer service staff, and customers who use funding products. The results of the study indicate that the decline in returns can affect customer loyalty, as reflected in fluctuations in the amount of Third Party Funds (DPK) and the number of customers. However, the bank implements strategies such as improving service quality, adopting a personal approach, maintaining intensive communication, and providing appreciation to customers. In addition, a soft selling strategy is applied in offering products so that customers continue to feel comfortable and valued. These strategies have proven effective in maintaining customer trust and loyalty despite the decrease in returns.